AMBIGUITAS DALAM JUDUL DONGENG ANAK - varia virdania virdaus (Universitas Narotama, 2021)
If there is ambiguity in the title of a fairy tale, the reader will struggle to understand it. This study aims to describe the ambiguity contained in several titles of children's fairy tales. The method used by the researcher is a qualitative method. After collecting and reducing the data, 4 (four) of 28 (twenty eight) fairy tale titles have ambiguity. The researcher analyzed the results and found that out of the 4 (four) titles, the categories of ambiguity were weak and grammatical level ambiguity. Weak ambiguity indicates that the phrase still has a lot of information to explore, while grammatical level ambiguity is when a group of words has different meanings. If the title is interpreted more than one meaning, it will cause confusion for the reader because it is not a universal meaning. Reading fairy tales has become a hobby for some children, especially if the fairy tale has an interesting title and is easy to understand. Keywords: fairy tale, Semantic, Ambiguity